Temporal and sequence-related variability in diffusion-weighted imaging of presumed cerebrovascular accidents in the dog brain - Boudreau, Elizabeth; Kerwin, Sharon C.; DuPont, Emily B.; Levine, Jonathan M.; Griffin, John F. (Frontiers in Veterinary Science, 2022)
Diffusion-weighted MRI (DWI) is often used to guide clinical interpretation of intraparenchymal brain lesions when there is suspicion for a cerebrovascular accident (CVA). Despite widespread evidence that imaging and patient parameters can influence diffusion-weighted measurements, such as apparent diffusion coefficient (ADC), there is little published data on such measurements for naturally occurring CVA in clinical cases in dogs. We describe a series of 22 presumed and confirmed spontaneous canine CVA with known time of clinical onset imaged on a single 3T magnet between 2011 and 2021. Median ADC values of < 1.0x10−3 mm2/s were seen in normal control tissues as well as within CVAs. Absolute and relative ADC values in CVAs were well-correlated (R2 = 0.82). Absolute ADC values < 1.0x10−3 mm2/s prevailed within ischemic CVAs, though there were exceptions, including some lesions of < 5 days age. Some lesions showed reduced absolute but not relative ADC values when compared to matched normal contralateral tissue. CVAs with large hemorrhagic components did not show restricted diffusion. Variation in the DWI sequence used impacted the ADC values obtained. Failure to identify a region of ADC < 1.0x10−3 mm2/s should not exclude CVA from the differential list when clinical suspicion is high.